2023
DOI: 10.3390/molecules28237786
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Methyl Red from Aqueous Solution Using Biochar Derived from Fennel Seeds

Dorota Paluch,
Aleksandra Bazan-Wozniak,
Robert Wolski
et al.

Abstract: In this study, fennel (Foeniculum vulgare) seeds were used as a precursor to obtain carbon adsorbents through physical activation with carbon dioxide and chemical activation by impregnating the precursor with sodium carbonate. The physical activation involved the carbonization of the precursor at a temperature of 600 °C for 60 min and activation at a temperature of 800 °C for 30 min with carbon dioxide. Chemical activation included impregnation of the precursor with sodium carbonate at a mass ratio of a precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Considering the surface analysis of the carbon materials tested, it can be concluded that there are several mechanisms by which methyl red can be adsorbed on the surface of biochar. Interactions between an adsorbent and adsorbate can occur through electrostatic attraction to a positively or negatively charged surface, π–π interactions involving aromatic rings or hydrogen bonds [19] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the surface analysis of the carbon materials tested, it can be concluded that there are several mechanisms by which methyl red can be adsorbed on the surface of biochar. Interactions between an adsorbent and adsorbate can occur through electrostatic attraction to a positively or negatively charged surface, π–π interactions involving aromatic rings or hydrogen bonds [19] …”
Section: Resultsmentioning
confidence: 99%
“…Interactions between an adsorbent and adsorbate can occur through electrostatic attraction to a positively or negatively charged surface, π-π interactions involving aromatic rings or hydrogen bonds. [19] Table 2 displays the acid-base properties of the biochar samples. The precursor exhibits a slightly acidic surface property, as evidenced by a pH value of 6.6 in its aqueous extract.…”
Section: Biochar Characterizationmentioning
confidence: 99%
“…A PlasmaQuant PQ 9000 Elite spectrometer (Analytic, Jena, Germany) was used. The measurement procedure is described in our earlier work [ 34 ]. The concentration of oxygen functional groups on the surface of the activated carbons was assessed using the Boehm method [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…One of the simplest and most effective methods for removing dyes from post-production water is adsorption [ 4 ], which involves binding dye molecules on the sorbent’s surface. The most popular sorbents today include activated carbons [ 5 ], which consist mainly of elemental carbon, the characteristic feature of which is a very extensive surface area, exceeding 500 m 2 /g [ 6 ]. These sorbents have been proved effective in removing most industrial dyes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%